CANNED MEAT PRODUCTS FOR MEMBERS OF THE SERBIAN ARMED FORCES: Na, K, Ca, AND Mg CONTENT AND HEALTH RISKS/BENEFITS - Stojanović, Branislav; Stojanović, Zdenka; Marjanović, Sonja; Janković, Saša; Antić, Mališa; Balaban, Milica; Antic, Vesna (Journal of Agricultural Sciences (Belgrade), 2022)
Macroelements such as Na, K, Ca, and Mg play a significant physiological role, and their inadequate intake has been linked to severe diseases such as high blood pressure. Data on risk assessment for human health in Serbia, from the intake of these macroelements through the consumption of canned food, are minimal. Therefore, the content of Na, K, Ca, and Mg in five types of canned meat that members of the Serbian Armed Forces regularly use was examined. Macroelements were determined by inductively coupled plasma mass spectrometry in cans of beef goulash, pork ragout, spam, liver pate, and meatballs in tomato sauce, which were stored from one month to six years. The sodium content was significantly higher than the potassium in all types of food, so the Na/K ratio below 1, desirable for good health, was not found in any of the analyzed products. Also, a significant number of samples had an unfavorable Ca/Mg ratio above 1. However, due to the low consumption of canned food by members of the Serbian Armed Forces, its contribution to the average daily intake of macroelements is almost negligible. The concentration of macroelements decreased with the shelf life, while a significant source of Ka and Mg, among analyzed ingredients, was red ground pepper.